Penyelesaian Sengketa Investasi Internasional : Apakah Penyelesaian Dapat Dilakukan Melalui International Court Of Justice (ICJ)? - Hanifah Fathhurrohmah, Aisyah (UI Scholars Hub, 2024)
The International Court of Justice, also known as the ICJ, is the principal organ of the United Nations based in The Hague, Netherlands. This institution was established in 1945 to resolve disputes between countries peacefully. The authority of the International Court of Justice is divided into two categories: Ratione Personae jurisdiction, which pertains to who is eligible to bring a case to the ICJ, and Ratione Materiae jurisdiction, which concerns the types of disputes that the ICJ can handle. The ICJ's jurisdiction includes examining cases, providing opinions/advisories, and adjudicating disputes submitted to it. The ICJ is not limited to specific types of cases and can also handle investment disputes brought before it. This paper aims to explain how the ICJ functions as a forum for resolving investment disputes by analyzing the issues faced by the Barcelona Traction, Light and Power Company Limited, which was declared bankrupt by the Catalonian government of Spain and subsequently brought before the ICJ. The parties involved in this dispute include the Spanish government as the host country of foreign investment, Canada as the country where the parent company is incorporated, and Belgium as the country whose nationals are the majority shareholders. This lawsuit was submitted to the ICJ because, at the time, there was no specialized dispute resolution body for investor-state disputes. Hence, the Barcelona Traction case was brought to the ICJ as the international dispute resolution body.